2010
DOI: 10.2753/atp1084-1806320103
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Experiences with Bullying in Higher Education

Abstract: Although much research has been done on workplace aggression and bullying over the past two decades, academics have paid relatively little attention to bullying in their own institutions. In this article, we discuss what is currently known about bullying in academia, with a particular focus on faculty behavior, and apply empirical and conceptual findings from research on aggression and bullying in other work settings and the significant literature on conflict management in higher education. We begin by describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
198
4
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(231 citation statements)
references
References 26 publications
(24 reference statements)
8
198
4
8
Order By: Relevance
“…Leymann (1996: 168) Mobbing is a world-wide problem in universities as in all modern workplaces. Strict hierarchy; wide authority of administrators; academic jealousy; hostile attitude of students; lack of job security; and working in the same department for a long time (Bozdag, 2009;Karatuna and Gök, 2012;Keashly andNeuman, 2010, Yıldırım andYıldırım, 2010) may be seen as main organizational factors of mobbing. Some academicians may be exposed to mobbing during a period of their careers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leymann (1996: 168) Mobbing is a world-wide problem in universities as in all modern workplaces. Strict hierarchy; wide authority of administrators; academic jealousy; hostile attitude of students; lack of job security; and working in the same department for a long time (Bozdag, 2009;Karatuna and Gök, 2012;Keashly andNeuman, 2010, Yıldırım andYıldırım, 2010) may be seen as main organizational factors of mobbing. Some academicians may be exposed to mobbing during a period of their careers.…”
Section: Discussionmentioning
confidence: 99%
“…Bunlar; akademik yükselme kriterlerinin zorluğu; üniversitelerdeki hiyerarşik yapının katı olması; rektör, dekan ve bölüm başkanlarına verilen mutlak ve geniş yetkiler; akademisyenlerin hem ders verme hem de yükselebilmek amacıyla bilimsel araştırma yapma zorunluluğu; akademisyenler arası kıskançlık; öğrencilerin düşmanca tutumu; doçent ve profesörler dışında iş güvencesinin olmaması; uzun süre aynı bölümde çalışma olarak özetlenmektedir (Bozdağ, 2009;Karatuna ve Gök, 2012;Keashly ve Neuman, 2010;Yıldırım ve Yıldırım, 2010). Lester (2009), üniversitelerde güç ve yetkinin meslektaşlar arasında sıklıkla el değiştirmesinin de işyerinde psikolojik taciz nedeni olabileceğini öne sürmektedir.…”
Section: İşyeri̇nde Psi̇koloji̇k Taci̇z Ve Akademi̇unclassified
“…The control measures inherent to managerialism often involve performance management systems, performance measures and targets. Keashly and Neuman (2010) found that performance management systems threaten faculty members' authority to direct their own work and interfere with collegiality. Such feedback is considered not collegial because it violates the norm of professional respect.…”
Section: Managerialism In Universitiesmentioning
confidence: 99%
“…Westhues (1998Westhues ( , 2004Westhues ( , 2006 and Friedenberg (2008) specified that emotional abuse is observed most commonly in health and higher education organizations. Even though the number of studies related to the mobbing of the academicians in universities has increased (Keashly & Neuman, 2010;Taylor, 2012, p. 15), there are still less number of studies in Turkey (Erkutlu & Chafra, 2014). When we consider that academic organizations are the guards of the realities, detectors of new facts, the protector of the community values, the molder of the youth and the pathfinder of the future (Kaya, 1993), faculties of education have important roles in the training of particularly teachers who have effective and crucial roles in the building of the community.…”
Section: The Current Studymentioning
confidence: 99%